Integrating Technological Advancements to Improve Pedagogical Quality in Drafting Technology - Abelgos, Aileen H.; Maroma, Dolly P.; Maroma, Allen N. (Future Science / FSH-PH Publications, 2025)
The accelerating demands of the Fourth Industrial Revolution (4IR) highlight the need to integrate technological advancements in education, particularly in technical-vocational fields like Drafting Technology. This study employed a descriptive-survey design to assess the competencies, pedagogical practices, and institutional support mechanisms of 35 Drafting Technology faculty members. Results indicated that while faculty displayed strong teaching commitment, subject matter expertise, and capacity to promote independent learning, gaps remained in professional certifications, industry immersion, and access to adequate facilities. Respondents reported active engagement in curriculum review and affective support for students; however, challenges included outdated equipment, limited modern laboratory resources, and uneven credentialing. These findings suggest the importance of continuous faculty development programs to strengthen technological proficiency, pedagogical adaptability, and industry alignment. In response, a one-year Drafting Technology Faculty Development Program was proposed, emphasizing advanced software training, industry immersion, and capacity-building initiatives.